Thidambu nritham of Malabar: A preliminary analytical study of ritual and cultural tradition in Northern Kerala - Puthumana, Govindan Namboothiri; Puthumana, Govindan (Abdul Media Literasi, 2025)
The northern part of Kerala state is known as Malabar region and thidambu nritham is a unique ritualistic dance form customary in the region. It is a dance with the replica of the presiding deity on the head. This paper explores the characteristics of key rituals, percussion accompaniment, rhythms and legends connected to thidambu nritham involving presentation of the results of the preliminary analytic research. Thidambu nritham is the last event among the sequence of events such as sreebhoothabali, processions, ashtapadi and chendamelam. The geometry as well as shape of the frame used to decorate thidambu correspond to the region in which the festival is organized. King Kolathiri was the patron of the event which began in a rough and ready form in the 13th century AD which combined shaivism (concept of sivapurana) and vaishnavism (concept of kaliyamarddana) prevalent in those days in the south India.